solve the equation of 5(X+2)-2(3-4x)=3(X+5)-4(4-x)​

Question

solve the equation of 5(X+2)-2(3-4x)=3(X+5)-4(4-x)​

in progress 0
Anna 1 month 2021-08-13T14:14:49+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-13T14:16:42+00:00

    Step-by-step explanation:

    5(X+2)-2(3-4x)=3(X+5)-4(4-x)

    =>(5x+10)-(6-8x)=(3x+15)-(16-4x)

    =>5x+10-6+8x=3x+15-16+4x

    =>13x+4=7x-1

    =>6x=-5

    =>x= -5/6

    Note:bring same variables nearby

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )